Effect of Perceived Organizational Support (POS), Servant Leadership and Islamic Work Environment on Employee Performance with Organizational Citizenship Behavior (OCB) as A Moderating Variable (Study at Bank Tabungan Negara Syariah KC. Solo) - Arsyad, Muhammad Rafly Aulia; Mochlasin, Mochlasin (IAIN Kudus, 2024)
This research wants to know several factors that can influence employee performance at Bank Tabungan Negara Syariah KC Solo. The research aims to reveal what factors can influence the performance of employees of the Solo KC State Sharia Savings Bank. This research uses a quantitative method by processing primary data obtained through a questionnaire given to employees of the Syariah State Savings Bank KC Solo, 40 respondents using a saturated sampling technique. Then the data obtained was processed using SPSS version 23. The analysis used in this research included instrument tests, statistical tests, classical assumption tests and Moderated regression analysis. Based on the test results, the results show: 1) perceived organizational support has a positive and significant effect on employee performance. 2) servant leadership has a positive and significant effect on employee performance. 3) an Islamic work environment has a positive and significant effect on employee performance. 4) organizational citizenship behavior has a positive and significant effect on employee performance. 5) organizational citizenship behavior does not moderate the influence of perceived organizational support on employee performance. 6) organizational citizenship behavior does not moderate the influence of servant leadership on employee performance. 7) organizational citizenship behavior does not moderate the influence of an Islamic work environment on employee performance.